2016
DOI: 10.1002/adem.201500533
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Behavior of Cracked Giant Magnetostrictive Materials in Three‐Point Bending under Magnetic Fields: Strain Energy Density Criterion

Abstract: In this paper, the fracture behavior of cracked giant magnetostrictive materials has been investigated both numerically and experimentally. Works in literature have been revisited, focusing on iron and rare-earth alloys, such as Terfenol-D. Three-point bending tests have been carried out on precracked specimens and the fracture loads have been measured in the presence and absence of a magnetic field. Recent studies on local stress fields in proximity of crack tips have shown that the Strain Energy Density (SED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 26 publications
(32 reference statements)
1
9
0
Order By: Relevance
“…It has been found that the critical radius of 0.07 mm, obtained from Equation 13 and recommended in a previous work (Colussi et al, 2016) without considering the loading rate, falls within the range of variation here proposed. In the next figure (Fig.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…It has been found that the critical radius of 0.07 mm, obtained from Equation 13 and recommended in a previous work (Colussi et al, 2016) without considering the loading rate, falls within the range of variation here proposed. In the next figure (Fig.…”
Section: Resultssupporting
confidence: 79%
“…The mesh adopted to compute W had the same grade of refinement adopted in a previous work by the present authors (Colussi et al, 2016), in which models with 6400 elements were used to evaluate the energy release rate by means of J-integral on the same geometry.…”
Section: Finite Element Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Colussi et al [166] performed finite element analyses and also discussed the effect of a magnetic field on Terfenol-D fracture resistance in terms of the energy release rate and average strain energy density. Colussi et al [166] performed finite element analyses and also discussed the effect of a magnetic field on Terfenol-D fracture resistance in terms of the energy release rate and average strain energy density.…”
Section: Electromagnetic Fracture Behaviormentioning
confidence: 99%
“…www.advancedsciencenews.com www.aem-journal.com alloy with a crack under a magnetic field and discussed the effect of the field on the fracture load. Colussi et al [166] performed finite element analyses and also discussed the effect of a magnetic field on Terfenol-D fracture resistance in terms of the energy release rate and average strain energy density. The results showed that the fracture load of cracked Terfenol-D alloys, under mode I loading, was greater in the absence of the magnetic field and decreased as the magnetic field increased.…”
Section: Electromagnetic Fracture Behaviormentioning
confidence: 99%